Crescimento de Enterolobium contortisiliquum (Vell.) Morong em formações florestais secundárias em Santa Maria, RS - Lira, David Fagner de Souza e (2016)
This study aimed to evaluate the influence of dendrometric, morphometric and qualitative variables in the annual periodic increment in basal area free of trees and under competition Enterolobium contortisiliquum. (Vell.) Morong. with a view to making decisions about the management of the species. The study was conducted in the state's central region of Rio Grande do Sul, in the city of Santa Maria. Subjects were measured and collected the dendrometric, morphometric and qualitative variables. Step data of the last 5 years were obtained by analysis of growth roller collected using the auger Pressler. To determine the density of the trees in the forest, it was calculated basal area in hectare per sampling point based on Bitterlich methodology. The timbaúva differs between the conditions in their dendrometric and morphometric variables, but individuals under competition vary more among themselves that free individuals of competition. The height of the bole in individuals free competition and the variables scope Index and formal canopy in individuals under competition does not suffer variation with increasing DAP values. The shape of the crown of free competition individuals ranges from tolerable perfect, the perfect cup is seen mostly in people over 40 cm DAP. In people under competition exists a variation of forms of canopy are assigned to most individuals as classification of good cup. The crown density of free individuals and under competition is lower in individuals under 40 cm DAP. Individuals under competition have canopy characteristics, being classified as to their sociological position in dominant and codominant. The better the shape and density of the canopy greater the slope of the land and the classification of sociological position in individuals at greater competition will be the height of the shaft. The crown diameter of individuals is estimated as a function of diameter breast height by simple linear model DC = - b0 + b1 * √dap for both conditions. The height of the bole of free individuals of competition has a growth behavior defined by average of 2.20 m approximately, being characteristic of the species forking near the base in the absence of competition. In individuals under competition the stem height can be explained in terms of diameter at breast height the equation HF=b1*√dap. Under competition, the total height is influenced by the density of the population differing in level to the conditions existing the need for using separate models, estimated by the equation HT=b1*√dap+b2*G(bit) and the free individuals competition for equation HT=b1*√dap. The growth in basal area of E. contortisiliquum can be estimated by analysis of stem growth rings and there are differences in growth between the two conditions. The IPAG the competition of free individuals is explained due to the DAP and individuals under competition is explained in terms of DAP and increase the qualitative proximity of water variable.